Atmospheric Sounding from Fengyun-3C GPS Radio Occultation Observations: First Results and Validation - Shuanggen Jin; Chao Gao; Junhai Li (Advances in Meteorology)
Carrying global positioning system (GPS) radio occultation (RO) receiver, Chinese meteorological satellite Fengyun-3C (FY-3C) was launched on September 23, 2013, which provides new observation data for observations and studies of weather and climate change. In this paper, the results of FY-3C GPS RO atmospheric sounding are presented for the first time, including high-order ionospheric correction, atmospheric parameters estimation, and evaluation by COSMIC and radiosonde observations as well as applications in estimating gravity wave activities. It is found that the effect of the ionospheric correction residual on the phase delay is below 20 mm, which has minimal impact on bending angle estimation and generates differences of about 1 K in the average temperature profile. The difference between FY-3C and COSMIC temperatures at all heights is within 1°C, and the tropopause temperature and height have a good consistency. Deviations from Radiosonde measurements are within 2°C, and the tropopause temperature and height results also have a strong consistency. Furthermore, global gravity wave potential energy is estimated from FY-3C GPS RO, exhibiting similar behavior to results derived from COSMIC radio occultation measurements. The mean value of the gravity wave potential energy near the equator is 10 J/kg and decreases toward the two poles while in the northern hemisphere, it is stronger than that in the southern hemisphere.